PENCEGAHAN COVID 19 BERBASIS PENDIDIKAN DI DESA ADAT KELUSA, KEC. PAYANGAN, KAB. GIANYAR - I Gusti Bagus Wirawan; Ni Putu Ayu Mirah Anggrima Wati (UNHI Press, 2021)
Currently, the Covid-19 virus has become a pandemic that has hit several countries in the world including Indonesia. The Covid-19 virus poses a very dangerous threat to the survival of the community. This case began with information submitted by the World Health Organization (WHO) on December 31, 2019, which stated that there were cases of pneumonia cluster cases with unclear etiology in Wuhan City, Hubei Province, China. This case continues to grow until there are reports of deaths and importations outside China. This causes the world community to be increasingly restless. Until now, in Indonesia, the spread of the Covid-19 virus has spread to various regions, with 340,622 people affected, 263,296 recovered and 12,077 people dead. Meanwhile in Bali Province itself, there were 10,304 people who have been exposed to the Covid-19 virus, 8,975 people who have recovered and 332 people who have died. Therefore, Community Service activities in the form of Real Work Lectures at the Indonesian Hindu University in this period were more directed at helping the community in the area of ​​origin of each student for prevention, breaking the chain of spreading Covid-19, increasing community resilience to be alert, alert. And resilient in facing the disaster of the Covid-19 virus outbreak. There are several work programs designed in this activity, such as (1) economics which includes; help check the real condition of merchandise at BumDes, collect data on MSMEs in Kelusa Village, and promote MSMEs in Kelusa Village. (2) educations includes; educating on how to wash hands properly and correctly to prevent transmission of the Covid 19 virus through online mode, Spread of stickers about the prevention of the Covid-19 virus. (3) The health sector includes; Distribution of masks and handzanitisers, invitations to join Laughter Yoga activities, and do mutual cooperation to clean the environment of the village of Kelusa. From these programs everything has gone well and has been responded positively by the people of Kelusa village.